Socialization of Strategy to Improve Student Learning Outcomes through Learning Discipline - Nur Wahyuni; Dinda Widyastika; Bambang Sutejo; Muhammad Aldo (Outline Journal of Community Development, 2023)
Improving students' academic performance is a primary focus in higher education, with discipline in studying being a key factor that affects academic success. However, many students face challenges in time management and developing effective study habits. Therefore, this community service activity aims to socialize strategies for enhancing academic performance through study discipline. The socialization was carried out through workshops and seminars, covering topics such as time management, effective learning techniques, intrinsic motivation, and the use of digital technology to support learning. The activity involved students from various majors selected through purposive sampling, focusing on students with lower to moderate GPAs and those who lacked effective study habits. The evaluation was conducted using both quantitative and qualitative methods. The results of the pre-test and post-test showed a significant improvement in students' understanding of study discipline, with an average score increase of 28.75 points. Qualitative evaluation also revealed positive changes in students' study habits, such as better time management, avoiding procrastination, and using digital tools like time management applications. Furthermore, the level of student satisfaction with the activity was high, reaching 86.25%, indicating that most students found the socialization activity highly beneficial. Based on these results, this activity proved effective in enhancing students' study discipline and can serve as a model for improving learning outcomes in higher education. Moving forward, it is recommended to provide follow-up sessions and continuous support to help students consistently apply study discipline in their academic lives.